Effect of Prabhanjanavimardanam Taila Nasya in Cervical Spondylosis - An Interventional Single Arm Study (International Journal of Ayurveda and Pharma Research, 2025)
Cervical spondylosis is a long-term degenerative disease of the neck spine that impacts the bones and discs of the neck, as well as the spinal canal components. Currently, it is seen among both young and middle-aged individuals, as a result of inactive lifestyles and higher levels of work-related strain. In Ayurveda, cervical spondylosis can be clinically compared to Apabahuka, Viswachi or Greevastambha, with Nasya seen as a cost-effective and efficient treatment option. Prabhanjanavimardanam Taila, which is referenced in the Tailaprakarana of Sahasrayoga, is recommended for treating Ashiti vatarogas through methods such as Pana, Abhyanga, Nasya, and Basti karma. Prabhanjanavimardanam Taila serves as a pacifier for Vata and Kapha, as well as reducing swelling and it is strengthening, and rejuvenating. After taking into account both the Dosa kopa and vitiated Dosa sthana, Nasya treatment with Prabhanjanavimardanam Taila was chosen. Materials and Methods: The research was planned as an interventional before-after study. Twenty-five individuals who met the inclusion-exclusion criteria were chosen from the Panchakarma Outpatient Department of Government Ayurveda College Panchakarma Hospital, Poojappura, Thiruvananthapuram. Nasya karma was given to them in the evening (4-5pm), with 8 bindu (4 ml) in each nostril, for 7 days. Evaluations were conducted using Visual Analog Scale (VAS) for pain and numbness, and Oswestry Disability Index (ODI) for neck pain. Results and Discussion: The results were statistically analysed using Wilcoxon's signed rank test. Significant decreases in symptoms were observed across all these factors. The outcome remained consistent during a 14-day follow-up period. Conclusion: The research findings indicate that the use of Prabhanjanavimardanam Taila Nasya for seven consecutive days shows effectiveness in decreasing symptoms in individuals with Cervical spondylosis (CTRI/2022/06/043112).